MORAL DUALISM IN RAPPACCINI’S DAUGHTER AND THE STRANGE CASE OF DR. JEKYLL AND MR. HYDE = SỰ SONG PHƯƠNG CỦA ĐẠO ĐỨC TRONG TÁC PHẨM RAPPACCINI’S DAUGHTER VÀ THE STRANGE CASE OF DR. JEKYLL AND MR. HYDE - Nguyễn, Thị Thanh Ngân (2021)
The idea about dual existence of the good and evil within human mind has been recorded in different religious theories such as Yin and Yang or Moral dualism in Zoroastrianism. Noticably, this has also become the source of inspiration for many writers to create significant literary works. Rappaccini’s Daughter and The strange case of Dr. Jekyll and Mr. Hyde are the two outstanding works of this theme. This research investigates the two above-mentioned literary works to find out in details the illustration of moral dualism or the co-existence of good and bad in each character. Besides, the research also analyzes the relationship between science and humanism from the perspective of moral dualism as this is the mutual theme exploited in both works. Researcher carries out profound analysis involving intensive reading and data collection from the two literary works and other related sources. Results show that the majority of characters in Rappaccini’s daughter and The strange case of Dr. Jekyll and Mr. Hyde possess both good and evil sides and display them in their actions throughout the stories. The relationship among science and humanity in this story can be considered as a two-way one as science only satisfíes the selfish desire of individuals instead of contributing to the sake of the majority.